PENGARUH PENGELOLAAN MODAL KERJA DAN PIUTANG TERHADAP PROFITABILITAS PADA PERUSAHAAN SUB SEKTOR PULP AND PAPER YANG TERDAFTAR DI BURSA EFEK INDONESIA - Fransiska Sihotang; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine the effect of working capital and receivables management on profitability in pulp and paper sub-sector companies listed on the Indonesia Stock Exchange. Working capital management as an independent variable uses the working capital turnover ratio, and receivables as an independent variable using the receivable turnover ratio (RTO). Profitability as the dependent variable uses the ratio of return on assets (ROA). The sampling technique used purposive sampling technique and obtained as many as 7 companies. The data in this study uses secondary data and financial statements. The data analysis used is using financial ratios and multiple linear regression with SPSS 24. The results of this study indicate that working capital management has no effect on profitability, accounts receivable has no effect on profitability, and the simultaneous test (f test) shows the effect of working capital and accounts receivable management variables on profitability in pulp and paper sub-sector companies listed on the Stock Exchange. Indonesia. Keywords: Working Capital Turnover, Receivable Turnover, and Profitability.